To determine which expression represents \( A \) such that \( A = 5 - \frac{11}{3} \), we should first calculate \( 5 - \frac{11}{3} \).
-
Convert \( 5 \) to a fraction with a denominator of \( 3 \): \[ 5 = \frac{15}{3} \]
-
Now, we can perform the subtraction: \[ A = \frac{15}{3} - \frac{11}{3} = \frac{15 - 11}{3} = \frac{4}{3} \]
Now, we can compare \( \frac{4}{3} \) with the provided options:
-
A = \( \frac{15}{3} + \frac{1}{3} \) \[ \frac{15}{3} + \frac{1}{3} = \frac{15 + 1}{3} = \frac{16}{3} \quad (\text{not equal to } \frac{4}{3}) \]
-
A = \( \frac{12}{3} + \frac{1}{3} \) \[ \frac{12}{3} + \frac{1}{3} = \frac{12 + 1}{3} = \frac{13}{3} \quad (\text{not equal to } \frac{4}{3}) \]
-
A = \( \frac{12}{3} - \frac{1}{3} \) \[ \frac{12}{3} - \frac{1}{3} = \frac{12 - 1}{3} = \frac{11}{3} \quad (\text{not equal to } \frac{4}{3}) \]
-
A = \( -\frac{12}{3} + \frac{1}{3} \) \[ -\frac{12}{3} + \frac{1}{3} = \frac{-12 + 1}{3} = \frac{-11}{3} \quad (\text{not equal to } \frac{4}{3}) \]
None of the given expressions equals \( A \) when calculated in context with \( A = \frac{4}{3} \).
It appears all responses do not provide a correct representation for \( A \) based on the original equation \( A = 5 - \frac{11}{3} \). In short: The result we found doesn't match any of the provided expressions for \( A \).